Tai Chi/Qigong in Adults with Depression and Anxiety: A Pilot Retrospective Study - Julia Novielli; Karin Cinalioglu; Angela Potes; Zo? Thomas; Joseph Inhaber; Marouane Nassim; Susanna G. Torres-Platas; Linda Morin; Johanne Drapeau; Rebecca Fox; Suzanne Rouleau; Aileen Castro; et al. (Mary Ann Liebert, 2022)
Objective: Treatment options for individuals suffering from depression and anxiety are limited in terms of both accessibility and feasibility. Finding alternative, scalable, and cost-effective treatments remains important. This study aimed to investigate the efficacy and feasibility of a 13-week Tai Chi/qigong intervention in the treatment of depression and anxiety. Methods: Sixty-six adult psychiatric outpatients (mean age 47.83???15.30 years) were recruited to participate in a 13-week Tai Chi/qigong program. Measures of depression (Patient Health Questionnaire [PHQ-9]), anxiety (General Anxiety Disorder-7 [GAD-7]), and insomnia (Athens Insomnia Scale-8 [AIS-8]) were compared pre- and post-intervention. Feasibility was measured using the Acceptance Feasibility Questionnaire. Results: Participants who completed the 13-week intervention (n?=?31) reported significant reductions in depression (d?=??0.67), anxiety (d?=??0.70), and insomnia symptomatology. Participants who completed the Tai Chi/qigong intervention reported enjoying the intervention and exercises, and having little difficulty in setting a home practice. Conclusions: Findings suggest that Tai Chi/qigong interventions may be an accessible, well-tolerated, and cost-effective intervention for psychiatric outpatients suffering from depression and anxiety. Limitations from the pilot study identify the use of small sample sizes and lack of an active control group. Larger randomized control trials that include active control groups are warranted.